Role of Land Asset Officers on The Installation of Certificate Liability Rights Who Died - Dian Melina (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2020)
Mortgage is a security right that is imposed on land rights as referred to in Act No. 5 of 1960 concerning Basic Agrarian Principles, along with other objects which are an integral part of the land, for the settlement of certain debts, which provide positions that give priority to certain creditors over other creditors. There are still those who use the name of a certificate of ownership right who has passed away for the installation of mortgage. The purpose of this research is to find out the role of land deed maker officials in the installation of mortgages with the name of a certificate of ownership that has passed away, which is carried out by the process of Inheritance to Inheritance Based on Justice. Problems is the process of inheriting inheritance to an inheritance based on justice, and how to overcome the problem of the role of land deed-making officials in the installation of mortgage rights under the name of a certificate of ownership that has passed away, which is carried out by the process of Inheritance to Justice-based Inheritance. This study uses a normative juridical approach, in data collection it is more emphasized on the decomposition and interpretation of data related to legal principles. The results are; The Role of Land Deed Making Officials in the Installation of Mortgage Rights with the Name of Ownership Certificates that have Died, which is carried out by the Inheritance process to Inheritance Based on Justice.